PERANCANGAN COMPANY PROFILE INTERAKTIF BERBASIS VIDEO CLIP STUDI KASUS DI STUDIO ATLANTIS SEMARANG - setiyo adi nugroho; Andri Cahyo Wijayanto (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
The field of video shooting services in the Semarang area is currently spread in almost every area of ​​the city. Ranging from small businesses to large companies. This service is generally needed to capture important moments in the form of video documentation. Studio Atlantis is a line of business that provides video shooting and editing services. This company was founded in 2010, having its address at jl. Pete Raya, Now. In addition to video shooting, Studio Atlantis also provides photography services. Marketing in this studio still uses simple media, .using a list of products in the form of digital images on a computer in explaining products to consumers. This method is less effective when showing product samples because you have to open a different application in another file location. The solution to this problem requires a media to help promote the products at Studio Atlantis to consumers in a more practical way. A company profile that summarizes company information along with product samples in the form of video clips then packaged into an interactive form.